Questioning the Meaning of Financial or State Economic Losses in Corruption Crimes After the Constitutional Court Decision Number 25/PUU-XIV/2016 - Airlangga, Rendy; Abidin, R.B. Muhammad Zainal; Mahendra Suhartono; Purwoleksono, Didik Endro (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Constitutional Court Decision Number 25/PUU-XIV/2016 has changed Articles 2 paragraphs (1) and 3 of the Eradication of Corruption Crime Law from formal criminal act to material criminal act, so that state losses must be interpreted as actual losses. On the basis of that decision, this research analyses the original intent or ratio legis of the word "can" in Articles 2 paragraphs (1) and 3 of the Eradication of Corruption Crime Law, which is useful to understand the spirit underlying the formulation of the word 'can’ or ‘formal criminal act’ since the inception of the Law. In addition, this research also reconstructs the meaning of financial losses or the state economy based on aspects morality. This research is doctrinal research that uses statute, conceptual, and case approaches. The results of this study conclude that the formulation of the word "can" in Articles 2 Paragraphs (1) and 3 of the Eradication of Corruption Crime Law is intended to facilitate proof of corruption in the field of finance or the state economy in Indonesia, whose modus operandi is increasingly sophisticated and complicated. However, corruption crimes are not only about financial or economic losses that must be proven and can be calculated but also moral losses that cannot be seen and calculated. Therefore, the reconstruction of the meaning of potential loss in Articles 2 paragraphs (1) and 3 of the Eradication of Corruption Crime Law in the future is very important to save the nation's morals.